Segregation behavior of iron in metallurgical grade silicon during SiCu solvent refining. (July 2016) - Huang, Liuqing; Lai, Huixian; Lu, Chenghao; Gan, Chuanhai; Fang, Ming; Xing, Pengfei; Li, Jintang; Luo, Xuetao
Abstract: Impurity removal from metallurgical grade silicon (MG-Si) is an important issue for solar-grade silicon production, and solvent refining is used as an effective method to purify silicon. To evaluate the purification ability of solvent refining with SiCu melt at 1343–1603 K, the effective segregation ratio of the main impurity element Fe between solid Si and SiCu melt was experimentally and theoretically determined. The results demonstrated that the effective segregation ratio of Fe increased with the increasing temperature at the range of 1343–1603 K. The corresponding removal mechanism of Fe was investigated in detail. It was found that the effective segregation ratio of Fe calculated by Scheil equation presented the same tendency with experimental results, and the theoretical calculation was more consistent with experimental results when back diffusion was considered. Moreover, Fe was found to form SiFeMn and FeMnTi phases into SiCu alloy phase from MG-Si with the presence of Cu. It can be concluded that removal mechanism of Fe was not only a segregation process, but also a recombining process of impurity phase transformation. Highlights: Segregation ratio of Fe in MG-Si during SiCu alloy solvent refining was analyzed. Effect of back diffusion on the segregation of Fe was studied. Phase transformation of Fe during the solidification process was observed.